Analysis of acute and late toxicity of adjuvant radiotherpy in women with cervical and endometrial cancer - Wareńczak-Florczak, Żaneta; Roszak, Andrzej; Włodarczyk, Hanna; Wojciechowska-Łącka, Arleta (Contemporary Oncology/Współczesna Onkologia, 2011)
Background : In case of pure prognostic factors women with cervical and endometrial cancer after surgical operation need to be treated with radiotherapy . Every radiation treatment may be involved with toxicity, acute and late. Material and methods : Performed was detailed analysis of 173 patients with cervical (38) and endometrial (135) cancer. We evaluated early and late post radiation reactions in all patients. Results : Acute reactions were found in 48.5% and late toxicity was found in 9.8% of patients. Women with endometrial cancer were significantly older then patients with cervical cancer (p < 0.002). Higher percentage of acute and late toxicity was observed from the bowel tah urinary tract (26% and 22.5% – acute; 8.1% and 1.73% – late). Higher percentage of acute side effects was observed in patients with cervival than with endometrial cancer (60.5% and 33.7%). Late post radiation reaction predominate also in patient with cervical cancer (13.2% and 8.9%). The adverse effects were associated with prolonged time of treatment due to breaks in radiotherapy. Higher percentage of breaks was found in older patients, more frequent in patient with endometrial than in cervical cancer group (7.4% and 2.6%).To conclude early postradiation reaction appeared more frequently, than late post radiation reactions. It was stated that early and late post radiation reaction appear more frequently in women with cervical than in endometrial cancer. Interruption in radiation delivery was longer than seven days in group with endometrial cancer that leads to extension of complete radiation treatment.